Assessing the Delivery of Community Policing Services in Ada County, Idaho, 2002 - Crank, John P. ([Verlag nicht ermittelbar], 2006)
This study was conducted to explore the ways that enable the Ada County Sheriff's Office (ACSO) to examine its behavior in five areas that embody its adoption of community policing elements: (1) periodic assessments of citizens' perceptions of crime and police services, (2) substation policing, (3) patrol based in problem-oriented identification and resolution, (4) performance evaluation in a community-oriented policing (COP)/problem-oriented policing (POP) environment, and (5) the building of community partnerships. The researchers strived to obtain both transitive and recursive effects. One of the goals of this project was to facilitate the ACSO's efforts toward self-reflection, and by doing so, become a learning organization. In order to do this, data were collected, via survey, from both citizens of Ada County and from deputies employed by the ACSO. The citizen survey was a random, stratified telephone survey, using CATI technology, administered to 761 Ada County residents who received patrol services from the ACSO. The survey was designed to correspond to a similar survey conducted in 1997 (DEVELOPING A PROBLEM-ORIENTED POLICING MODEL IN ADA COUNTY, IDAHO, 1997-1998 [ICPSR 2654]) in the same area regarding similar issues: citizens' fear of crime, citizens' satisfaction with police services, the extent of public knowledge about and interest in ideas of community policing, citizens' police service needs, sheriff's office service needs and their views of the community policing mandate. The deputy survey was a self-enumerated questionnaire administered to 54 deputies and sergeants of the ACSO during a pre-arranged, regular monthly training. This survey consisted of four sections: the deputies' perception of crime problems, rating of the deputy performance evaluation, ethical issues in policing, and departmental relations.